2018
DOI: 10.1057/s41285-018-0076-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress, domination and basic income: considering a citizens’ entitlement response to a public health crisis

Abstract: In 2015/16, stress was found psychologically to be responsible for 37% of work-related illnesses and 45% of working days lost due to illness in Great Britain. Stress has also been linked to long-term chronic health conditionsincluding heart disease, stroke, cancer, type 2 diabetes, arthritis and depressionresponsible for 70% of NHS England spend, 50% of GP appointments, 64% of outpatient appointments and 70% of inpatient bed days. It is apparent that medical responses to stress-related illness contribute to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Some of this study’s authors have argued elsewhere that Universal Basic Income (UBI) may serve to mitigate these social determinants of health [ 11 , 12 ]. Indeed, their model of impact [ 12 p411] sets out the likely causal pathways between welfare systems, UBI specifically, and health outcomes via pathways of poverty reduction, inequality reduction and predictability and security of income which are likely to result in improved satisfaction of material needs, behavioural change that encourages longer-term investment in health and stress reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Some of this study’s authors have argued elsewhere that Universal Basic Income (UBI) may serve to mitigate these social determinants of health [ 11 , 12 ]. Indeed, their model of impact [ 12 p411] sets out the likely causal pathways between welfare systems, UBI specifically, and health outcomes via pathways of poverty reduction, inequality reduction and predictability and security of income which are likely to result in improved satisfaction of material needs, behavioural change that encourages longer-term investment in health and stress reduction.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have reported that the health sector suffers the most from this type of problem [ 13 , 14 , 15 ]. In line with this data, occupational stress has become one of the most relevant problems for public and occupational health [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects derived from work stress suppose important direct and indirect consequences for public health [ 16 , 37 ]. They generate an expense to the system due to high demand on health services, and the necessity of treatments that must be maintained in the long term like antidepressants or anxiolytics, which have a minimum duration of several months [ 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…By reducing poverty and enabling people to overcome periods of unemployment, UBI reduces “health inequalities and the structural conditions that put people ‘at risk of risks,’” such as “discrimination, poverty, residential segregation, inadequate schools, unemployment” (Thoits, 2010, p. S47). Existing evidence suggests that, by acting as a safety net of predictable, certain income, UBI reduces psychological stress (see Johnson & Johnson, 2019; Kangas et al, 2019, p. 25) as well as having “modest to strong positive effects on a range of health outcomes, including low birth weight, adult and child mental health, service use, and diet” Gibson, Hearty, and Craig, (2018, p. 11).…”
mentioning
confidence: 99%